The Palgrave Handbook of Global Citizenship and Education (Palgrave Macmillan UK, 2018)
This Handbook is a much needed international reference work, written by leading writers in the field of global citizenship and education. It is based on the most recent research and practice from across the world, with the 'Geographically-Based Overviews' section providing summaries of global citizenship and education provided for Southern Africa, Australasia, Europe, the Middle East, North America, Latin America, and East and South East Asia. The Handbook discusses, in the 'Key Ideologies' section, the philosophies that influence the meaning of global citizenship and education, including neo-liberalism and global capitalism; nationalism and internationalism; and issues of post-colonialism, indigeneity, and transnationalism. Next, the 'Key Concepts' section explores the ideas that underpin debates about global citizenship and education, with particular attention paid to issues of justice, equity, diversity, identity, and sustainable development. With these key concepts in place, the 'Principal Perspectives and Contexts' section turns to exploring global citizenship and education from a wide variety of viewpoints, including economic, political, cultural, moral, environmental, spiritual and religious, as well as taking into consideration issues of ethnicity, gender and sexuality, and social class. Finally, the 'Key Issues in the Teaching of Global Citizenship' section discusses how education can be provided through school subjects and study abroad programmes, as well as through other means including social media and online assessment, and political activism. This Handbook will be vital reading for academics, postgraduates and advanced undergraduates in the fields of sociology and education, particularly those with an interest in comparative studies.